Trace Metal Concentration and Sea Water Quality of Tuzla Shipyard Area, Istanbul, Turkey Using Mediterranean Mussels (Mytilus galloprovincialis) for Monitoring Aquatic Pollution - (:unkn) unknown (ZOOLOGICAL SOC PAKISTAN, 2016)
The mussels of the genus Mytilus have been proposed for routine biomonitoring programs to evaluate pollutants such as heavy metals in coastal environments. The concentrations of Pb and Cd were determined in Mytilus galloprovincialis (n=200) caught from the Tuzla area of Istanbul, Turkey between May 2013 and April 2014. The Cd level was found to be low whereas concentrations of Pb in mussels collected from 4 stations exceeded acceptable levels for human consumption according to the legal standards of Turkish Food Codex and United Nations Environment Programme.
Keywords: Cadmium; lead; Mytilus galloprovincialis; shipyard; harbour; SURFACE SEDIMENTS; COAST; BOSPORUS; LEAD; CD; PB